Recurrent Urinary tract infections and type 2 diabetes mellitus: a systematic review predominantly in women - Papp, Sara B.; Zimmern, Philippe E. (Frontiers in Urology, 2023)
Background: Type 2 diabetes mellitus is considered a risk factor for developing recurrent urinary tract infections. This review examined current knowledge on the incidence rates, bacterial strains, risk factors, treatments, and outcomes of recurrent urinary tract infections in type 2 diabetes, predominantly in women. Methods: A systematic review was conducted for all English language articles from inception to June 2022 utilizing the Cochrane and Preferred Reporting Items for Systematic Reviews and Meta-Analyses standards in the databases PubMed, OVID Embase, and Cochrane Library. References were cross-examined for further articles. Data collected described the prevalence, characteristics, and management of recurrent urinary tract infections. Risk of bias assessments were performed for all studies. Results: From 3342 identified articles, 597 met initial study criteria. Fifteen studies from 10 countries were included after full-text reviews. Four studies found higher recurrent urinary tract infection rates in diabetics versus non-diabetics meanwhile others reported recurrence rates from 23.4% to 37%. Four of five studies found diabetes to be a risk factor for recurrent urinary tract infection. E. coli was the most frequent causative pathogen. Antibiotic prescription results varied; however, multiple studies determined that longer treatment (≥ 5 days) did not correlate with lower recurrence rates. Risk of bias assessments found the most frequent study weakness to be identification of confounding variables. Conclusions: This review covered multiple subtopics, with few comprehensive or generalizable results, suggesting a need for more research on how recurrent urinary tract infections can be better evaluated and managed in women with type 2 diabetes.